2023
DOI: 10.1002/cpt.2932
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Trimethoprim on Thiamine Absorption: A Transporter‐Mediated Drug‐Nutrient Interaction

Abstract: Trimethoprim is predicted to inhibit several thiamine transporters, including the primary thiamine intestinal absorptive transporter, ThTR‐2, and the hepatic and renal organic cation transporters, OCT1, OCT2, and MATEs. To investigate the effect of trimethoprim on thiamine absorption, studies were conducted in cells, mice, and healthy volunteers and supported by use of real‐world data. In a randomized, crossover clinical study, seven healthy volunteers were given a single oral dose of thiamine or thiamine plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Isobutyryl carnitine has also been recently suggested as a potential OCT1 biomarker (Luo et al, 2020). OCT1 inhibitors ritlecitinib and trimethoprim decreased plasma isobutyryl carnitine concentration as OCT1 mediates the net efflux of isobutyryl carnitine out of hepatocytes (Vora et al, 2023, in agreement with the reduced plasma isobutyryl carnitine level in subjects carrying the OCT1 mutation (Jensen et al, 2021). Inhibition on both BCRP-mediated efflux and OCT1-mediated uptake in the intestine and liver, respectively, may explain the lack of effect of BMS-986371 on plasma isobutyryl carnitine.…”
Section: Discussionmentioning
confidence: 99%
“…Isobutyryl carnitine has also been recently suggested as a potential OCT1 biomarker (Luo et al, 2020). OCT1 inhibitors ritlecitinib and trimethoprim decreased plasma isobutyryl carnitine concentration as OCT1 mediates the net efflux of isobutyryl carnitine out of hepatocytes (Vora et al, 2023, in agreement with the reduced plasma isobutyryl carnitine level in subjects carrying the OCT1 mutation (Jensen et al, 2021). Inhibition on both BCRP-mediated efflux and OCT1-mediated uptake in the intestine and liver, respectively, may explain the lack of effect of BMS-986371 on plasma isobutyryl carnitine.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to THTR2 ablation, administration of the THTR2 inhibitor trimethoprim also reduced brain thiamine. Our recent study investigating the impact of trimethoprim on thiamine disposition showed that elevations in plasma thiamine was accompanied by a decline in hepatic thiamine ( p = 0.067) [ 53 ], likely through a combined effect on OCT1 and THTR2. Importantly, the changes in tissue thiamine despite normal circulating levels indicates that plasma and RBC thiamine status markers may not reflect tissue status when transporter function is compromised.…”
Section: Discussionmentioning
confidence: 99%
“…Future clinical interaction studies associated with these drugs and thiamine disposition changes are highly recommended; transporters beyond THTR2 should be also considered. Evidence for this expansion involves recent clinical and animal data showing an unexpected increase in systemic thiamine concentrations upon the administration of trimethoprim, an antifolate antibiotic with THTR2-inhibitory properties [ 32 ]. This increase in systemic thiamine concentrations was believed to result from the simultaneous inhibition of thiamine hepatic uptake and its clearance via OCT1 by trimethoprim.…”
Section: Disruption Of Thiamine Absorptionmentioning
confidence: 99%
“…Reduced thiamine uptake in Caco-2 and THTR2-overexpressing HEK293 cells [29][30][31] Trimethoprim (5.6 µM)-direct inhibitor Increased plasma thiamine concentration in patients [32] Reduced thiamine uptake in Caco-2 and THTR2-overexpressing HEK293 cells [30] Metformin (680 µM)-direct inhibitor Reduced thiamine uptake in THTR2-overexpressing HEK293 cells [31] Hydroxychloroquine (17 µM)-unknown if direct/indirect inhibitor Reduced thiamine uptake in THTR2-overexpressing HEK293 cells [31] Verapamil (141 µM)-unknown if direct/indirect inhibitor Reduced thiamine uptake in THTR2-overexpressing HEK293 cells [31] Folate uptake by PCFT Sulfasalazine (60 µM)-direct inhibitor Reduced folate and methotrexate uptake in PCFT-overexpressing oocytes [33] Lactate uptake by MCT1 Phloretin (NA)-direct inhibitor Reduced lactate uptake in MCT1-overexpressing oocytes [16,34] Gabapentin enacarbil/XP-13512 (0.62 µM)-direct inhibitor Reduced lactate uptake in Caco-2 cells and MCT1-overexpressing HEK293 cells and oocytes [34,35] Quercetin (NA)-direct inhibitor Reduced lactate uptake in MCT1-overexpressing oocytes [16,34] AR-C155858 (NA)-direct inhibitor Reduced lactate uptake in MCT1-overexpressing oocytes [16] ADZ3965 (17 nM)-direct inhibitor Metabolic acidosis risk; increased urinary elimination of lactate and ketone; no changes in lactate plasma concentrations in patients [36,37] Cholesterol uptake by NPC1L1 Ezetimibe (24 µM)-direct inhibitor Reduced cholesterol uptake in NPC1L1-overexpressing MDCKII cells [38] Reduced dietary cholesterol absorption in patients [39] Bile acid transport by ASBT Maralixibat (0. Beyond the gliflozins, other drugs have been linked to the inhibition of glucose transport.…”
Section: Onset Of Wernicke's Encephalopathy In Patientsmentioning
confidence: 99%